11 Impact of weaning strategy on calf performance, behavior, and activity - Ott, Grace C (J Anim Sci, 2019)
Weaning is known to be the most stressful time in a beef calf’s post-natal life. Weaning stress may have long-term impacts on cattle performance. This study was conducted to determine differences in calf stress under three weaning strategies. Two hundred twenty-nine Angus or Angus-Simmental cross pairs at two locations were assigned to one of three weaning treatments: abrupt removal of the calf on d 0 (Abrupt, n = 77), fenceline contact for 7 d prior to removal of the calf on d 7 (Fence, n = 79), and abrupt removal of the calf on d 84 (Late, n = 73). Behavioral observations were conducted pre- and post-weaning and total activity was measured prior to and after weaning using accelerometers placed on collars on five calves per treatment. Calf weights, hip heights, and body condition scores (BCS) were collected to evaluate calf performance post-weaning. Data were analyzed using PROC MIXED of SAS. Statistical significance was determined at P < 0.05 and a tendency at 0.05<p<0.10. Skeletal growth via hip height was not affected by weaning treatment. During the first 28 d after initial weaning, the Abrupt calves lost while the Late weaned calves gained weight (-0.09 and 0.49 kg/d, respectively; P < 0.05). Fence were intermediate weight and tended to be different from both treatments (0.02 kg/d; P = 0.09). Overall ADG was not affected (P > 0.10) by timing or strategy of weaning. Total activity was greater (P < 0.05) in Abrupt than Fence on d 1 and d 2 post-wean (Abrupt 26772 and 22346 and Fence 22235 and 16691 relative activity units/hour, respectively). Calf activity was elevated (P < 0.05) on day of weaning until d 2 post-wean then returned to pre-wean level by d 3 for all treatments. Short-term differences in calf performance warrant further exploration of the possible long-term effects on heifer development and steer feedlot performance.